2016
DOI: 10.1515/tnsci-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

The neonatal levels of TSB, NSE and CK-BB in autism spectrum disorder from Southern China

Abstract: Background: Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder that impairs a child's ability to communicate with others. It also includes restricted repetitive behaviors, interests and activities. Symptoms manifest before the age of 3. In the previous studies, we found structural abnormalities of the temporal lobe cortex. High spine densities were most commonly found in ASD subjects with lower levels of cognitive functioning. In the present study, we retrospectively analyzed medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
8
0
4
Order By: Relevance
“…NSE values will provide more accurate results in the first two years of life, called a critical period for brain development. Thus, a retrospective study by Nv et al found that NSE was higher in ASD children in the neonatal period (Lv et al, 2016). Furthermore, as the integrity of the blood brain barrier may not always be disrupted, increased NSE levels may not be reflected sufficiently in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSE values will provide more accurate results in the first two years of life, called a critical period for brain development. Thus, a retrospective study by Nv et al found that NSE was higher in ASD children in the neonatal period (Lv et al, 2016). Furthermore, as the integrity of the blood brain barrier may not always be disrupted, increased NSE levels may not be reflected sufficiently in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…This study retrospectively compared ASD and healthy control groups in the neonatal period. Accordingly NSE was clearly high in the neonatal period in children with ASD (Lv et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Arrows indicate a significant increase or decrease in mRNA or protein levels, ns denotes no significant difference between schizophrenia and controls, -denotes that this measurement was not performed. of NSE and CK-BB in the ASD group compared to controls [150]. Lv and colleagues also found that within the ASD group, the levels for both these brain-specific molecules were significantly higher in low-functioning ASD individuals compared to high-functioning ASD individuals.…”
Section: Markers Of Bbb Permeability In Asdmentioning
confidence: 91%
“…Wang et al [29] reported hypermethylation of the NSE gene in 14.5% of autistic children, as well as decreased NSE RNA expression. Higher neonatal serum NSE has also been reported in patients with ASD compared to controls [30].…”
Section: Introductionmentioning
confidence: 86%
“…In addition, since S100B increases ROS at high concentrations and triggers apoptosis, we also aimed to assess levels of M30, M65, and active caspase-3, associated with apoptosis, and to examine the relation between these parameters and S100-tau in patients with ASD. Additionally, we also intended to examine levels of NSE, reported at high levels in patients with neonatal autism [30], in our patient group and to examine its relations with S100B, tau and apoptosis. There is also still no recognized biomarker for the early diagnosis of ASD.…”
Section: Introductionmentioning
confidence: 99%